2022
DOI: 10.1155/2022/2582192
|View full text |Cite
|
Sign up to set email alerts
|

Existence of Fixed Points in Fuzzy Strong b-Metric Spaces

Abstract: In the present research, modern fuzzy technique is used to generalize some conventional and latest results. The objective of this paper is to construct and prove some fixed-point results in complete fuzzy strong b-metric space. Fuzzy strong b-metric (sb-metric) spaces have very useful properties such as openness of open balls whereas it is not held in general for b-metric and fuzzy b-metric spaces. Due to its properties, we have worked in these spaces. In this way, we have generalized some well-known fixed-poi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Sitara et al [36] proposed q-rung picture fuzzy (q-RPF) graph structures and numerous significant results for modeling with q-RPF graph. Kanwal et al [37] proposed the existence of fixed points in fuzzy strong b-metric spaces, and Kanwal and Azam [38] gave the notion of common fixed points of IFS maps for Meir-Keeler type contractions. Many AOs for different extensions of fuzzy sets are proposed in [39,40].…”
Section: Introductionmentioning
confidence: 99%
“…Sitara et al [36] proposed q-rung picture fuzzy (q-RPF) graph structures and numerous significant results for modeling with q-RPF graph. Kanwal et al [37] proposed the existence of fixed points in fuzzy strong b-metric spaces, and Kanwal and Azam [38] gave the notion of common fixed points of IFS maps for Meir-Keeler type contractions. Many AOs for different extensions of fuzzy sets are proposed in [39,40].…”
Section: Introductionmentioning
confidence: 99%
“…Then, Öner showed that every "open" ball in a fuzzy strong b-metric space is an open set. Since then, fuzzy strong b-metric spaces have received the attention of some researchers (see, e.g., [33][34][35]).…”
Section: Definitionmentioning
confidence: 99%
“…Ishtiaq et al [17] derived several FP results in generalizations of FMSs. In fuzzy strong b-metric spaces, Shazia et al [18] identified FPs for a number of nonlinear contraction mappings. In 2004, Park [19] used the idea of intuitionistic FSs, continuous t-norm (CTN), and continuous t-conorm (CTCN) to established intuitionistic fuzzy metric spaces (IFMSs) as a generalization of FMSs.…”
Section: Introduction and Prelimainariesmentioning
confidence: 99%